Insight into the crystal synthesis, activation and application of ZIF-20 - Seoane, Beatriz (2011)
The crystallization of the zeolitic imidazolate framework ZIF-20 has been tuned from the point of view of crystal size and aggregation by using rotation and seeding with a previously prepared material. In addition, the activation of ZIF-20 by solvent extraction has been found to be in correlation with the relative permittivity of the solvent. High permittivity solvents (acetone and methanol) extract more guest dimethylformamide but amorphize the structure, while those with low permittivity (n-pentane and chloroform) preserve the crystallinity of ZIF-20. The dispersion in commercial polysulfone of the small synthesized ZIF-20 particles obtained with low aggregation results in an improved O2-selective mixed matrix membrane (O2 permeability and O2/N2 selectivity being 1.0 (±0.0) Barrer and 6.7 (±0.5), respectively).